Solving the dilemma between maritime security and trade : in search of the most effective approach - Yue, Sophia Qi Hui. (2011)
After the September 11 incident and a rise in piracy attacks, there has been a growing concern and focus on maritime security. This is especially so with over 90 percent of the world’s trade being dependent on sea transportation. This has led to the creation of many maritime security initiatives to secure the future of business organisations. However, there is a lack of research in studying the factors which contribute to a successful security initiative implementation. This study aims to investigate and come up with an effective management model which balances maritime security and organisation efficiency for the shipping and port organisations.